2014
DOI: 10.1165/rcmb.2013-0264oc
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Binding Cassette Transporter 1 Attenuates Ovalbumin-Induced Neutrophilic Airway Inflammation

Abstract: Apolipoprotein A-I (apoA-I) is an important component of highdensity lipoprotein particles that mediates reverse cholesterol transport out of cells by interacting with the ATP-binding cassette transporter 1 (ABCA1). apoA-I has also been shown to attenuate neutrophilic airway inflammation in experimental ovalbumin (OVA)-induced asthma by reducing the expression of granulocyte colony-stimulating factor (G-CSF). Here, we hypothesized that overexpression of the ABCA1 transporter might similarly attenuate OVA-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…The increased neutrophilic airway inflammation in OVA-challenged Apoa1-deficient mice was also associated with increases in type 1 (IFN-g) and type 17 (IL-17A) cytokines, but not type 2 cytokines (IL-4, IL-5, and IL-13). Similarly, OVA-challenged mice that overexpressed the human ABCA1 transporter under the Tie2 promoter in pulmonary vascular endothelial cells and macrophages had attenuated increases in BALF neutrophils and G-CSF as compared with wild-type mice (59). Collectively, these studies showed that an apoA-I/ABCA1-dependent pathway inhibited experimental OVA-induced neutrophilic airway inflammation by reducing G-CSF production.…”
Section: Apoa-i and Asthmamentioning
confidence: 71%
“…The increased neutrophilic airway inflammation in OVA-challenged Apoa1-deficient mice was also associated with increases in type 1 (IFN-g) and type 17 (IL-17A) cytokines, but not type 2 cytokines (IL-4, IL-5, and IL-13). Similarly, OVA-challenged mice that overexpressed the human ABCA1 transporter under the Tie2 promoter in pulmonary vascular endothelial cells and macrophages had attenuated increases in BALF neutrophils and G-CSF as compared with wild-type mice (59). Collectively, these studies showed that an apoA-I/ABCA1-dependent pathway inhibited experimental OVA-induced neutrophilic airway inflammation by reducing G-CSF production.…”
Section: Apoa-i and Asthmamentioning
confidence: 71%
“…To gain insight into ABCA13 biology, we can examine other ABCA family members: Abca1-KO mice have impaired lipid transport resulting in reduced serum cholesterol and HDL, elevated intracellular lipid contents, and abnormal lung structure 41 . In contrast, mice over-expressing human ABCA1 gene showed reduced inflammation and pathology in a model of allergic lung inflammation 42 . In humans and mice, dysfunction of ABCA3 results in surfactant deficiencies and fatal respiratory failure 12,43,44 .…”
Section: Discussionmentioning
confidence: 96%
“…OVA-challenged Tie2-hABCA1 transgenic mice, which conditionally overexpress the human ABCA1 transporter under the Tie2 promoter in vascular endothelial cells and macrophages, have attenuated neutrophilic airway inflammation, airway epithelial wall thickness, and serum levels of OVA-specific IgE. 11 The attenuated neutrophilic airway inflammation in OVA-challenged Tie2-hABCA1 mice was associated with significant reductions in G-CSF protein expression by pulmonary vascular endothelial cells and alveolar macrophages, as well as reduced G-CSF protein levels in BALF. This outcome suggests that ABCA1 expression by vascular endothelial cells and macrophages may reduce allergen-induced neutrophilic airway inflammation by suppressing production of G-CSF.…”
mentioning
confidence: 99%
“…ApoA-I and ABCA1 are both expressed by alveolar epithelial cells and alveolar macrophages in the lung, whereas pulmonary vascular endothelial cells and airway smooth muscle cells also express ABCA1. [9][10][11][12][13][14] Mice with a genetic deletion of apoA-I have a phenotype of increased lung inflammation and oxidative stress, as well as enhanced AHR and collagen deposition. 15 In addition, levels of HDL, as well as the antioxidant protein paraoxonase 1, are reduced in Apoa1-deficient mice.…”
mentioning
confidence: 99%